2019
DOI: 10.3389/fnhum.2019.00006
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Flexibility in Dynamic Functional Connectivity Quantifies the Severity in Autism Spectrum Disorder

Abstract: Resting-state functional connectivity (FC) analyses have shown atypical connectivity in autism spectrum disorder (ASD) as compared to typically developing (TD). However, this view emerges from investigating static FC overlooking the whole brain transient connectivity patterns. In our study, we investigated how age and disease influence the dynamic changes in functional connectivity of TD and ASD. We used resting-state functional magnetic resonance imaging (rs-fMRI) data stratified into three cohorts: children … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 52 publications
10
96
0
Order By: Relevance
“…7). This follows previous work showing the engagement of brain networks is specific to the current behavior (Mattar et al, 2015; Telesford et al, 2016) and that disrupting these networks underlies numerous pathologies (Badhwar et al, 2017; Braun et al, 2016; Harlalka et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…7). This follows previous work showing the engagement of brain networks is specific to the current behavior (Mattar et al, 2015; Telesford et al, 2016) and that disrupting these networks underlies numerous pathologies (Badhwar et al, 2017; Braun et al, 2016; Harlalka et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…Meanwhile, increased variance of connectivity of the PCC to other DMN regions during the resting state was associated with slower reaction times on a subsequent attention task [Lin et al, ]. Moreover, recent DFC analyses showed that connection variability was positively correlated with the ADOS scores [Chen et al, ; Harlalka, Raju, Krishnanunni, & Roy, ], and higher variability was also observed in another study [Falahpour et al, ], which could cause unstable transmission between major brain hubs [Chen et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, global flexibility was highly negatively correlated with modularity, suggesting that more segregated networks are also more resistant to change, and thus exhibit lower variability across a certain time span (Harlalka, Bapi, Vinod, & Roy, 2019; Meunier, Lambiotte, & Bullmore, 2010; Ramos‐Nuñez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%